9 - L’énergie en Afrique et le plan d’action de Lagos - Smail KHENNAS (Africa Development, 1982)
In this article , the author outlines the energy policy in Africa in relation to the recommendations of the Lagos Plan of Action. He particu- larly emphasizes the need for recording the energy potentials of Afrìca and the conditions of their uses within the framework of a coordinated policy throughout the whole continent . . He focuses his analyses on fossil energy ( hydrocarbon , uranium , coal) and renewable energy (solar and hydro- electric energy). In his concluding remarks he suggests actions whose implementation could provide the basis for an energy policy in Africa Smail KHENNAS est chercheur au Centre de Recherche en Economie Appliquée (CREA) à Alger, Algérie